Financial Consumer Protection and the Cost of Financial Intermediation: Evidence from Advanced and Developing Economies - Pasiouras, Fotios (Management Science, 2018)
Using a data set of approximately 3,000 commercial banks from more than 100 countries, I examine the impact of financial consumer protection policies on the cost of financial intermediation. I find evidence that the existence of internal mechanisms for handling complaints, requirements for fair treatment, supervisory power related to consumer protection, and various disclosure requirements reduce the cost of financial intermediation in advanced countries. The results are different in the case of developing countries, where I observe that most financial consumer protection policies increase the cost of intermediation, suggesting that banks pass on regulatory burdens to their customers. This paper was accepted by Amit Seru, finance.